Characteristics of unintentional ingestion of oral non-steroidal anti-inflammatory drugs and analgesics in preschool children - Babić Željka; Kordić Nikolina Benco; Rešić Arnes; Turk Rajka (Arhiv za Higijenu Rada i Toksikologiju, 2021)
We characterised accidental ingestion of non-steroidal anti-inflammatory drugs and non-opioid analgesics in children aged 0–5 years between 2009 and 2019 by analysing records of telephone consultations with the Croatian Poison Control Centre (CPCC) and cases treated at the Children’s Hospital Zagreb (CHZ). Among the total of 466 identified cases (411 from CPPCC records and 55 from CHS hospital records), the most frequently ingested drugs were ibuprofen (47 %), paracetamol (20 %), ketoprofen (15 %), and diclofenac (11 %). In 94 % of the cases unsupervised children ingested the drug left within their reach. The remaining 6 % were dosing errors by parents or caregivers and involved liquid formulations as a rule. Our findings can serve as real-life examples informing preventive measures.